What about Asia? Revisiting Asian Studies - van der Velde, Paul; Stremmelaar, Josine (Amsterdam University Press, 2006)
What about Asia? Revisiting Asian Studies brings together scholars from Asia, Europe and America to test the strength of a field of study which, considering the rise of Asia, should be gaining momentum. But is it? This is one of the many questions that the contributors to this volume ask themselves. In the past decade the use and legitimacy of area studies, and in particular Asian studies, have been passionately debated in conferences and academic journals. What about Asia? gives the current state of the debate on Asian studies by tackling the issue from a multiregional and interdisciplinary perspective.